Age-related changes in prepulse inhibition of the startle response - de Oliveira, Yasmin Guedes; Poltronieri, Bruno Costa; Woodruff, Erica; da Costa, Brunno Freitas; Panizzutti, Rogerio Arena (Frontiers in Psychiatry, 2023)
Acoustic prepulse inhibition of the startle response (PPI) is a phenomenon characterized by the reduction in the startle reflex caused by the presence of a weak stimulus before an intense and sudden stimulus (pulse). These phenomena can be observed in several species, being commonly measured in humans by the eyeblink electromyography. PPI works as an operational measure of sensory-motor gating, which is the ability to suppress motor responses for sensory stimulus. Healthy aging is marked by several changes in neural processing, like inhibitory functioning decline. In this research we aim to investigate if PPI is reduced with aging and if this reduction would be associated with cognitive functioning of older adults. To this aim, we compared PPI levels of older adults (over 60 years old) with PPI levels of young adults (from 18 to 28 years old). With that, we found, in fact, lower PPI level and lower startle amplitude in older adults than in young adults. However, we did not find differences in levels of habituation and correlation between PPI and cognition within the sample of healthy older adults.Our results demonstrate that aging is a factor that affects PPI and that it does not seem to predict cognition, however, future studies should explore the potential of using PPI for cognitive changes associated with techniques such as cognitive training.